2020
DOI: 10.3390/ma13235342
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical In Vitro Assessment of Submicron-Scale Laser Surface Texturing on Ti6Al4V

Abstract: Loosening of orthodontic and orthopedic implants is a critical and common clinical problem. To minimize the numbers of revision surgeries due to peri-implant inflammation or insufficient osseointegration, developments of new implant manufacturing strategies are indicated. Ultrafast laser surface texturing is a promising contact-free technology to modify the physicochemical properties of surfaces toward an anti-infectious functionalization. This work aims to texture Ti6Al4V surfaces with ultraviolet (UV) and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
1
6
0
1
Order By: Relevance
“…The periodicity of ca. 400 nm is consistent with expected values for green light on titanium [35,36] …”
Section: Resultssupporting
confidence: 88%
“…The periodicity of ca. 400 nm is consistent with expected values for green light on titanium [35,36] …”
Section: Resultssupporting
confidence: 88%
“…Cunha et al [20] has reported that the Ti-6Al-4V LIPSS implant surface can potentially improve the osseointegration of titanium dental and orthopedic implants. Schweitzer [21], in a preclinical study, has found that human primary mesenchymal stromal cells (hMSCs) cells cultured on LIPSS surfaces were not compromised in terms of their viability.…”
Section: Discussionmentioning
confidence: 99%
“…jak i nanometrowej ze zredukowanym ryzykiem zanieczyszczenia tworzonej powierzchni. [6][7][8] W ostatnim czasie prowadzone są badania nad wykorzystaniem ultrakrótkiego pulsacyjnego lasera do opracowywania powierzchni wszczepów biomedycznych. [9][10][11] Technika ta pozwala na zogniskowanie wiązki promieniowania laserowego w krótkim czasie i na niewielkiej przestrzeni, co pozwala na uzyskanie laserowo indukowanej periodycznej struktury powierzchni (laser induced periodic surface structure -LIPSS).…”
Section: Conclusion 1-1 Laser-modified Hydroxyapatite Coating Present...unclassified